Selective Attention: a Comparative Study on Argentine Students from Different Socioeconomic Contexts - Ison, Mirta Susana (2015)
Attentional Efficiency (AE) is defined as the accuracy with which a child discriminates, from a group of similar stimuli, those which are identical to a model, within a certain time period. Various factors may be associated with a higher or lower AE, among which is socioeconomic context. The goals of this study were: 1) To describe argentine students' attentional efficiency according to the type of school (private-public), according to the students' age and gender and according to the educational and occupational level of the students' mothers; 2) To compare attentional efficiency according to the type of school (private-public), students' age and gender and educational and occupational level of their mothers. Method: A comparative cross-sectional study was used. Two groups of 10-to-13-year-old students were formed: 74 from public schools (Mean 11.26; S.D. 0.93; 53% boys and 47% girls) and 67 students (Mean 11.49; S.D. 1.05; 54% boys and 46% girls) from a private schools. Type of school is categorized by Mendoza general Board of Education. Private schools are located in urban areas. Public schools are situated in peripheral areas in contexts of social vulnerability. Social vulnerability is a condition of social risk that hinders, either immediately or in the long term, the satisfaction of welfare needs, both in terms of survival and quality of life. In this kind of contexts there are lower levels of education in the families, poor working conditions and/or unemployment, families dysfunction and poor mother and child health services. All of these situations lead to unequal social conditions and decreasing opportunities for children's development. There are 10 public schools in peripheral areas and 25 private schools in urban areas at Guaymallen, Mendoza. The participants were from two schools, one from public and other from private school. Results: The results revealed lower attentional efficiency in school children attending public schools than in those attending a private schools. No statistically-significant differences were observed in attentional efficiency in relation to the gender or age of the participating children. The students whose mothers had attained a university level of education showed a significantly higher attentional performance, in contrast with those students whose mothers had only attended primary school. In addition, the students whose mothers were employed showed a significantly higher attentional performance in contrast with those children whose mothers were unemployed. Nevertheless, no statistically-significant differences were observed in attentional efficiency in relation to occupational level of qualification of students' mothers. Conclusion: This study concurs with research showing the influence of socioeconomic context on children's attentional performance, contributing evidence on the need to adjust educational practices and cognitive interventions to boost children's academic achievements.